(3GdaJM GdbOSj hGdcTa GdCfSj aj hQO GdSMQs - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s
(3ChdgG (B:s
(3hHYO aGYde CjgG GdeQjO GdedGRe Ydi EbJWGa CRgGQ GdChQGO s
(3BNQgG (B:s
(3Gddge CfJ QHj dG Edg EdG CfJ Ydjc JhcdJ hCfJ QH GdYQT GdYXje JeJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B168s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs